(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The professor as a primary axis in education is a facilitator of relevant knowledge who has to be updated, and who looks for proper scenarios for training and tuning skills and pedagogic knowledge as part of one’s own personal, professional, and institutional commitment. Part of the professor’s activities is to include additional knowledge and skills to create an international and intercultural ethos, in students to connect with other cultures and in professors to share international and intercultural experiences. The objective of this descriptive quantitative study is to describe the activities related to the Internationalization of the curriculum as participants of the DePaul-UJAT program. To prove the hypothesis: bilingual professors with pedagogic training show a high teaching commitment toward the process of the Internationalization of the Curriculum in three dimensions: personal, professional, and institutional. The results obtained show a high commitment to the process. It is suggested to carry out further studies with the cohorts or different generations from the program in order to identify which one has a higher commitment.